The Quick and the Dirty: Best Practices for Writing and Editing Under Tight Timelines : Open Session Report - Panlilio, Stephany (AMWA Journal, 2022)
Conference Education Session Report Speakers J. Kelly Byram, MS, MBA, ELS, Immediate Past President and Director-at-Large for New Mexico, AMWA Southwest Chapter, Freelance Editor and Writer, Owner of Duke City Consulting, LLC, Albuquerque, NM Theresa E. Singleton, PhD, 2021 AMWA Fellow, Freelance Scientific Writer, Owner of Singleton Science, LLC, Beverly, MA Damiana Chiavolini, MS, PhD, President-Elect of AMWA Southwest Chapter, Academic Writer, Editor, and Instructor, Richardson, TX